Identification of altered brain metabolites associated with TNAP activity in a mouse model of hypophosphatasia using untargeted NMR‐based metabolomics analysis. Issue 6 (March 2017) - Cruz, Thomas; Gleizes, Marie; Balayssac, Stéphane; Mornet, Etienne; Marsal, Grégory; Millán, José Luis; Malet‐Martino, Myriam; Nowak, Lionel G; Gilard, Véronique; Fonta, Caroline
Abstract : The functions of tissue non‐specific alkaline phosphatase (TNAP) in the brain were investigated using NMR spectroscopy. Thirty‐nine metabolites were identified and quantified in whole brain extracts. Unsupervised statistical analysis revealed a strong distinction between TNAP‐knockout mice and their littermates based on three of these metabolites (GABA, cystathionine, adenosine). Five additional metabolites showed significantly altered levels in the knockout mice. This study reveals several metabolic pathways that directly or indirectly depend on TNAP (involving PLP‐dependent enzymes and nucleotide regulation) and helps to understand the neurological disorders of hypophosphatasia. Abstract: Tissue non‐specific alkaline phosphatase (TNAP) is a key player of bone mineralization and TNAP gene ( ALPL ) mutations in human are responsible for hypophosphatasia (HPP), a rare heritable disease affecting the mineralization of bones and teeth. Moreover, TNAP is also expressed by brain cells and the severe forms of HPP are associated with neurological disorders, including epilepsy and brain morphological anomalies. However, TNAP's role in the nervous system remains poorly understood. To investigate its neuronal functions, we aimed to identify without any a priori the metabolites regulated by TNAP in the nervous tissue. For this purpose we used 1 H‐ and 31 P NMR to analyze the brain metabolome of Alpl ( Akp2 ) mice null for TNAP function, a well‐described model of infantile HPP. Among 39 metabolites identified in brain extracts of 1‐week‐old animals, eight displayed significantly different concentration in Akp2 −/− compared to Akp2 +/+ and Akp2 +/− mice: cystathionine, adenosine, GABA, methionine, histidine, 3‐methylhistidine, N‐acetylaspartate (NAA), and N‐acetyl‐aspartyl‐glutamate, with cystathionine and adenosine levels displaying the strongest alteration. These metabolites identify several biochemical processes that directly or indirectly involve TNAP function, in particular through the regulation of ecto‐nucleotide levels and of pyridoxal phosphate‐dependent enzymes. Some of these metabolites are involved in neurotransmission (GABA, adenosine), in myelin synthesis (NAA, NAAG), and in the methionine cycle and transsulfuration pathway (cystathionine, methionine). Their disturbances may contribute to the neurodevelopmental and neurological phenotype of HPP.